Inventory management performance for family planning, maternal and child health medicines in public health facilities of West Wollega zone, Ethiopia - Oliyad Kebede; Gizachew Tilahun (Taylor & Francis Group, 2021)
Background Inventory management is the heart of the supply system in improving availability of medicines, reducing the cost, and improving patient care quality. However, in the government facilities' supply system, inventory management is poor. So, the purpose of this research is to assess inventory management performance for family planning, maternal and child health medicines in public health facilities of West Wollega zone, Oromia region, Ethiopia. Method Facility-based descriptive cross-sectional quantitative study was conducted using checklist, structured and semi-structured questionnaire, and triangulated with qualitative method. Quantitative data were coded and analyzed using SPSS Version 20 and Microsoft excel spreadsheet. Qualitative data were analyzed manually, using thematic analysis technique. Different indicators were used to measure variables. Results Among 23 health facilities assessed, availability of family planning/maternal and child health medicines ranged from 0 to 100%. Average availability of medicines was 14 (61.30%) with mean stock-out duration of 70.71 days. Bin cards were available for 559 (78.40%) of medicines, and 374 (52.45%) bin cards were accurate. Report submission rate was 116 (84.06%), with 47 (40.52%) report and resupply forms reported on time, 73 (62.93%) of them were complete and 69 (59.48%) were accurate. Supplier-related problem, lack of human resource, administrative problem, and lack of computer infrastructure were inventory management challenges identified. Conclusion Inventory management performance for Family planning/maternal and child health medicines was poor as indicated by low availability, high stock-out duration, and poor LMIS performance. Efforts should be undertaken by concerned bodies to improve it.